ANALISIS PENGARUH BRAND IMAGE, KUALITAS PRODUK, DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN SEPATU BASKET MEREK NIKE PADA ATLIT BASKET DI KOTA PONTIANAK - admin, Muhammad Panca Fernando B1021131011 (Jurnal Manajemen Update, 2017)
This research aims to find out how the effect of brand image, product quality, and celebrity endorser toward the purchase decision of nike basketball shoes on basketball athletes in Pontianak city. The method of this research is survey method and the object of this research is basketball athletes in Pontianak city. The analytical tool that used in this research is multiple linear regression analysis, before analyzing with multiple linear regression analysis, firstly, before the multiple linear regression, this research needs to conducting validity test, reliability test, and classic assumption test that includes normality test, linierity test, multikolinierity test, and heterokedasticity test to the data that already got. From the result of this research that used multiple regression analysis, simultaneously, the independent variables have a significant effect to the dependent variabel (purchase decision) with f counted at 46,424. Partially, brand image variable has significant effect to the purchase decision of nike basketball shoes with t counted at 4,116, product quality variable has significant effect to the purchase decision of nike basketball shoes with t counted at 4,486, and celebrity endorser variable has no significant effect to the purchase decision of nike basketball shoes with t counted at 1,202. Also, the coefficient of determination in this multiple linear regression is 59,2%, it describes the ability of the independent variables that include brand image, product quality, and celebrity endorser to influence toward the purchase decision of nike basketball shoes as the dependent variabel, while the other 40,8% influenced by other variables that is not included in this research. Keywords: brand image, product quality, celebrity endorser, and purchase decision